2015
DOI: 10.1007/s00167-015-3837-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported allergies cause inferior outcomes after total knee arthroplasty

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Hilton et al 31 found that increasing medical comorbidities (as determined by the Charlson index) postoperatively correlated with subsequent worsening of physical function and pain outcomes post-TKA. Hinarejos et al 32 found that patients with at least one self-reported allergy had worse postoperative outcomes in terms of the WOMAC and KSS knee scores for TKA than patients without allergies. They proposed that allergies could be considered a prognostic factor and possibly used when counselling TKA patients preoperatively.…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hilton et al 31 found that increasing medical comorbidities (as determined by the Charlson index) postoperatively correlated with subsequent worsening of physical function and pain outcomes post-TKA. Hinarejos et al 32 found that patients with at least one self-reported allergy had worse postoperative outcomes in terms of the WOMAC and KSS knee scores for TKA than patients without allergies. They proposed that allergies could be considered a prognostic factor and possibly used when counselling TKA patients preoperatively.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…They proposed that allergies could be considered a prognostic factor and possibly used when counselling TKA patients preoperatively. 32 Oberbek et al 33 found that increased body weight and a high BMI, above 35, influenced the level of pain severity in the operated knee joint and physical activity of the patient after the surgery. Their results indicated the need for further evaluation of BMI as a prognostic factor in the planning of physiotherapy in patients treated for idiopathic osteoarthritis of the knee joint after TKA.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…These results suggest that although antibiotic allergy may itself predict a longer length of stay and increased risk of complications (2)(3)(4), it is unlikely to be the dominant explanation for the findings we observed.…”
Section: Disclosures Of Conflicts Ofmentioning
confidence: 59%
“…The inclusion of such patients may have affected the results, as an association has been previously demonstrated between known or suspected penicillin allergy and increased number of hospital inpatient days as well as infection with pathogenic organisms such as Clostridium difficile and methicillinresistant Staphylococcus aureus (3). Another study of patients with a history of antimicrobial allergy similarly demonstrated an association with lengthier hospital stay, higher intensive care unit admission rate, and increased in-hospital mortality rate (4).…”
Section: Editormentioning
confidence: 99%
“…Various subspecialties, such as hip and knee arthroplasty, have evaluated this and shown that patients with multiple reported allergies have less improvement in patient-reported outcomes postoperatively compared with patients with fewer allergies. 1 - 3 This topic has also been investigated in shoulder arthroplasty; however, the results have been varied. A recent study by Rosenthal et al revealed that the presence of one or more self-reported allergies did not correlate with worse function, satisfaction, pain, or range of motion postoperatively.…”
Section: Introductionmentioning
confidence: 99%